2015
DOI: 10.1002/jat.3213
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity of superparamagnetic iron oxide nanoparticles on neuronal and glial cells. Evaluation of nanoparticle interference with viability tests

Abstract: Superparamagnetic iron oxide nanoparticles (ION) have attracted great interest for use in several biomedical fields. In general, they are considered biocompatible, but little is known of their effects on the human nervous system. The main objective of this work was to evaluate the cytotoxicity of two ION (magnetite), coated with silica and oleic acid, previously determining the possible interference of the ION with the methodological procedures to assure the reliability of the results obtained. Human neuroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 54 publications
5
59
0
Order By: Relevance
“…Physicochemical characterization of the O‐ION used in the present study was previously reported in Costa et al (). In brief, it showed that they are spherical particles with a magnetite core average diameter of 10.9 nm; the effectiveness of oleic acid coating was confirmed, because less than 7% of the nanoparticle surface presents iron.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Physicochemical characterization of the O‐ION used in the present study was previously reported in Costa et al (). In brief, it showed that they are spherical particles with a magnetite core average diameter of 10.9 nm; the effectiveness of oleic acid coating was confirmed, because less than 7% of the nanoparticle surface presents iron.…”
Section: Resultsmentioning
confidence: 90%
“…Accordingly, the present study aimed to evaluate the possible cytotoxic and genotoxic effects of O‐ION on human glial cells (A172 astrocytes). In a previous study conducted by our research group (Costa et al ), effects induced by O‐ION on viability of A172 glial cells were evaluated. Results showed that O‐ION induced a significant decrease in astrocytes viability, besides a serum‐protective effect was observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations